Degradation of Polycyclic Aromatic Hydrocarbons Contamination in Groundwater by Sodium Percarbonate Oxidation - Zhang, Yue-Hua; Sun, Yu-Gang; Yue, Li-Hong; Guo, Chang-Hong (Asian Journal of Chemistry, 2013)
Sodium percarbonate has been used to oxidize a wide range variety of organic and inorganic compounds in water under multiple conditions of environment of contamination in groundwater. Sodium percarbonate is effective showed over a wide pH ranges. Even though the theoretical dosage of [PAHs]/[2Na2CO3·3H2O2] even down to 0.4 for complete degradation of polycyclic aromatic hydrocarbons (PAHs), it still needed, at least, 3 mol of [2Na2CO3·3H2O2] to degradation this chemical dosage. This indicates that oxidation intermediates competed sodium percarbonate molecules with the parent polycyclic aromatic hydrocarbons. The primary pH has no obviously efficacy on polycyclic aromatic hydrocarbons decompose, for hydrogen-ions were conformation during the degradation of polycyclic aromatic hydrocarbons.